2017
DOI: 10.1097/md.0000000000008124
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water immersion delivery on the strength of pelvic floor muscle and pelvic floor disorders during postpartum period

Abstract: Background:Water immersion delivery is a non-pharmacological approach to ease labor pain. This paper aims to investigate the effect of water immersion delivery on increasing strength of pelvic floor muscle (PFM) and relieving pelvic floor disorders (PFDs) during postpartum period.Methods:A total of 2749 vaginal-delivery primiparas in postpartum 6-8 weeks were selected as research objects. Based on the modes of delivery, 600 patients were assigned into water immersion delivery group, 2149 were assigned into con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In China, episiotomy used to be a routine practice for vaginal delivery. 12 13 In the last decade, hospital data reported rates of 47.4%-84.7%, [14][15][16][17] and some multicentre studies reported hospital rates from 41.2% to 69.7%. 18 19 For China, where there were 17.23 million births in 2016, 20 there could be as many as 7.33 million episiotomies a year (given a vaginal birth rate of 61.0% and an episiotomy rate of 69.7% among vaginal births).…”
Section: Introductionmentioning
confidence: 99%
“…In China, episiotomy used to be a routine practice for vaginal delivery. 12 13 In the last decade, hospital data reported rates of 47.4%-84.7%, [14][15][16][17] and some multicentre studies reported hospital rates from 41.2% to 69.7%. 18 19 For China, where there were 17.23 million births in 2016, 20 there could be as many as 7.33 million episiotomies a year (given a vaginal birth rate of 61.0% and an episiotomy rate of 69.7% among vaginal births).…”
Section: Introductionmentioning
confidence: 99%
“…After 10 years of efforts, this project has been supported by many nongovernment organizations from both America and China [7] . Before the use of NA, common services provided in our delivery room include midwives service, accompanying family members, and water immersion service [9] during the first stage of labor if patients had requirement(about 20% of them chose water immersion delivery). With the help of NPLD, NA has been regularly carried out in our hospital since May 1st, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…After 10 years of efforts, this project has been supported by many nongovernment organizations from both America and China [7] . Before the use of NA, common services provided in our delivery room include midwives service, accompanying family members, and water immersion service [9] during the rst stage of labor if patients had requirement (about 20% of them choose water immersion delivery). NA has been regularly carried out in our hospital since May 1st, 2015.…”
Section: Introductionmentioning
confidence: 99%